Complementarity and Related Problems: a Survey - Kanzow, Christian; Ferris, Michael (My University, 1998)
This survey gives an introduction to some of the recent developments in the fields of complementarity and related problems. After presenting two typical examples and the basic existence and uniqueness results, we focus on some new trends for solving nonlinear complementarity problems. Extensions to mixed complementarity problems, variational inequalit8ies and mathematical programs with equilibrium constraints are also discussed
Keywords: complementaity